Penyuluhan Fisioterapi K3 untuk Postur Kerja dan Pencegahan Nyeri Leher di PT Alhasanie, Kalimantan Timur - Melisa Cindy Simbolon; Atika Yulianti (Pusat Riset dan Inovasi Nasional, 2025)
Introduction: Musculoskeletal Disorders (MSDs) are common health issues that occur in the workplace, particularly due to prolonged computer use with poor ergonomic posture. This condition is frequently experienced by employees in the Office Department of PT. Alhasanie, who often complain of neck pain caused by muscle tension. Objective: To evaluate the effectiveness of occupational physiotherapy (K3) education in improving workers' understanding of neck pain and its prevention through education and stretching exercises. Method: The study involved providing education to 32 workers, with pre-test and post-test evaluations to measure their improvement in understanding. Results: The findings indicate a significant increase in workers' knowledge regarding risk factors, symptoms, and preventive exercises for neck pain after attending the education session. Conclusion: Occupational physiotherapy (K3) education is effective in raising workers' awareness of the importance of proper posture and stretching exercises to reduce muscle tension caused by prolonged sitting.